SUSTENTABILIDADE DA PESCA ARTESANAL NO LAGO DE VIANA, ÁREA DE PROTEÇÃO AMBIENTAL DA BAIXADA MARANHENSE - Costa, Clarissa Lobato da (2006)
The artisan fishing is one of the main economic activities in the town of Viana. It involves an expressive amount of people daily practicing that activity. The objective of this study was to evaluate the artisan fishing considering the seasonality of the region, approaching the socio-economical and ecological dimensions for the sustainability of the activity. The methodology used was questionnaires and later the following of the fishery unloading to determine the destiny of the fishing product. It was also used the hydro balance calculation to consider fishing sustainable sceneries. The results demonstrated that even having a guaranteed daily food the fisherman is the one who has the lowest financial gain from the activity, living in very poor conditions. It was recorded in Viana Lake the existence of twenty-six species belonging to seventeen families and twenty-four genera. The species Plagioscion squamosissimus (south american silver croaker), Pygocentrus nattereri (red piranha) and Prochilodus nigricans (black prochilodus) occured during the whole year, being meaningful in the captures, while Schizodon vittatus (aracu) and Pimelodus omatus (bloch´s catfish) appeared more frequently in the rainy season. It can also be observed that Hoplias malabaricus (trahira) and Loricariichthys sp (loricaria), known as black fish appeared more frequently in the dry season. This paper presents as an alternative to the sustainability in the region sceneries related to damming up water through building small dams into canals. When it comes to fishing activities, though, investments in aquaculture, to promote the creation of native species in community could be an alternative as the area shows an irregular hydro period.